Teachers’ Attitudes Towards Teaching Mathematics to Third-Grade Male Students in Primary and Early Childhood Schools in Jeddah - Alshehri, Atheer Abdullah Turki; Khomais, Sama Fouad (Journal of Educational and Psychological Sciences, 2025)
Teachers’ attitudes are the invisible force that shapes the learning experience; they can either ignite curiosity or extinguish it. These attitudes help instill confidence and motivation in students—or undermine them. Based on this premise, the present study aims to explore the level of teachers’ attitudes toward teaching mathematics to third-grade male students in primary and early childhood schools in the city of Jeddah. To achieve this, an attitude scale covering three dimensions—cognitive, affective, and behavioral—was employed. The scale was administered to 74 male and 100 female teachers who teach mathematics to third-grade male students in primary schools. The results revealed no statistically significant differences between male and female teachers’ attitudes toward teaching mathematics. The findings also highlighted a high level of competence in the cognitive dimension, whereas the affective and behavioral dimensions received less focus. This indicates a need to enhance these two areas in order to create a more integrated learning experience. The findings further uncover an invisible gap between what is theoretically known and what is practically applied in the classroom. The study assumes that teachers’ attitudes represent a fundamental pillar in improving educational quality and that developing these attitudes across the cognitive, affective, and behavioral domains constitutes an effective approach to enhancing instructional performance in classrooms.